How Amazon Web Services Uses Formal Methods. - NEWCOMBE, CHRIS; RATH, TIM; FAN ZHANG; MUNTEANU, BOGDAN; BROOKER, MARC; DEARDEUFF, MICHAEL (Communications of the ACM, 2015)
The article discusses the use of formal specification and model checking by engineers at Amazon Web Services (AWS), a cloud computing platform offered by electronic commerce company Amazon.com, Inc., to help solve design problems in critical systems. Topics include AWS's use of distributed systems and cost-efficient infrastructure; the growth of Amazon's cloud computing services; and methods used to safeguard users' data. The use and modifications of fault-tolerant distributed algorithms is also explored.